The generalist as orchestrator: The case of art education in Geneva - Mili, Isabelle (Swiss Journal of Educational Research, 2022)
The teacher of the republican school (Coutel, 1999) is a conveyor of culture and, potentially, of encyclopaedic knowledge: a generalist! However, the generalist orchestrates interventions that are complementary to his or her own: traffic safety education, sex education, support for allophone pupils, rhythmic lessons, etc. In addition, cultural institutions welcome generalists and their classes. Through observations and interviews with 12 actors in these collaborations, this case study examines how, in Geneva, generalists and others educational actors define their collaboration - in the artistic and cultural field; and how the generalists consider their role within such a network of educational actions.